Comparative efficacy of three commercial vitamin and trace mineral premixes for rearing broiler chickens at starter and finisher phases - O., Oduguwa; B. K., Ogunmodede; A. O., Fanimo (Universiti Putra Malaysia Press, 1996)
Six groups of 45 unsexed day-old Hubbard broiler chicks were randomly assigned in duplicate at the starter phase (0-5 weeks) to three isocaloric and iso-nitrogenous diets which were fortified at manufacturers recommended levels with three commercial vitamin and trace mineral premixes purchased locally and labelled as premix A, U and Z. At the finisher phase (6 -9 weeks) the birds were shuffled and subdivided into three finisher treatment groups of two replicates each. One treatment group continued to receive the same premix as during the starter phase, while the other two groups were assigned the remaining premixes not given at the starter phase for that particular treatment group. Thus nine premix combinations were used at the finisher phase. The premix type fed at the starter phase led to differences (P > 0.05) in the protein intake, mean weight gain and weight gain per unit protein intake of the birds. Protein intake and weight gain per unit protein intake were not significantly different (P < 0.05) at the finisher phase. The serum uric and serum creatinine levels indicate that birds fed premix Z at the starter phase utilized the dietary protein more efficiently than those fed the other two premixes. Variable values were obtained for the serum metabolites at the finisher phase. It was concluded that available premixes for broilers in Nigeria vary in their content and their effect of protein nutriture ofbroiler chickens. It is recommended that if combinations of premixes are to be used in rearing broilers, care should be taken to feed a proven premix of good quality at the starter phase.